Morphological and molecular description of Myxobolus batalhensis n. sp. (Myxozoa, Myxosporea), a liver and ovary parasite of Salminus hilarii in Brazil - Vieira, Diego Henrique Mirandola Dias [UNESP]; Alama-Bermejo, Gema; Bartholomew, Jerri Lee; Abdallah, Vanessa Doro; de Azevedo, Rodney Kozlowiski (Springer Nature, 2017)
Plasmodia containing myxospores belonging to the genus Myxobolus Bütschli, 1882 were found in the ovaries and liver of Salminus hilarii. Despite its economic value, this fish host has no previous reports of myxozoan infections. Herein, we describe Myxobolus batalhensis n. sp. using morphological and ultrastructural data, as well as histological and SSU rDNA molecular data. The mature myxospores were elongated, measuring in average 15.2 ± 0.8 μm in length, 8.4 ± 0.4 μm in width, and 5.1 ± 0.2 μm in thickness. Polar capsules were elongated and measured 5.3 ± 0.3 μm in length and 2.8 ± 0.3 μm in width. Polar filaments had 6–9 coils. Histopathological analysis showed coagulation necrosis associated with cell lysis as a response of the host cell to the parasite in the ovaries. No inflammatory reaction was observed in the liver, although the presence of the plasmodia caused changes in tissue structure. The phylogenetic analysis of South American myxobolid species showed M. batalhensis n. sp. as sister species of Myxobolus aureus. This is the first report of a myxozoan species parasitizing S. hilarii and the first myxozoan species described in the Batalha river.
Keywords: Bryconidae; Histopathology; Myxobolidae; Phylogeny; SSU rDNA; Ultrastructure